2014
DOI: 10.1371/journal.pntd.0002719
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Attenuation of Chikungunya Virus by Adaptation to Heparan Sulfate-Dependent Infectivity: A Model for Rational Arboviral Vaccine Design

Abstract: Mosquito-borne chikungunya virus (CHIKV) is a positive-sense, single-stranded RNA virus from the genus Alphavirus, family Togaviridae, which causes fever, rash and severe persistent polyarthralgia in humans. Since there are currently no FDA licensed vaccines or antiviral therapies for CHIKV, the development of vaccine candidates is of critical importance. Historically, live-attenuated vaccines (LAVs) for protection against arthropod-borne viruses have been created by blind cell culture passage leading to atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 73 publications
(112 reference statements)
12
89
0
1
Order By: Relevance
“…Region 1 consists of peptides 380 to 382 (amino acids 3033 to 3066) and sits in the acid-sensitive region (ASR) of the E2 glycoprotein. The ASR is thought to play a critical role in regulating CHIKV virulence and regeneration (54,55). Interestingly, these data conform to earlier reports, from investigations of CHIKV-infected humans, nonhuman primates, and mice (30,49,52), that neutralizing antibodies tend to target this region.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Region 1 consists of peptides 380 to 382 (amino acids 3033 to 3066) and sits in the acid-sensitive region (ASR) of the E2 glycoprotein. The ASR is thought to play a critical role in regulating CHIKV virulence and regeneration (54,55). Interestingly, these data conform to earlier reports, from investigations of CHIKV-infected humans, nonhuman primates, and mice (30,49,52), that neutralizing antibodies tend to target this region.…”
Section: Resultssupporting
confidence: 89%
“…Here we examined the immunogenicity and efficacy of p62-E1 protein in the C57BL/6 mouse infection model (12,55) and showed that two immunizations with p62-E1 mixed with the AS03 or Matrix-M adjuvant were required to induce immunity against CHIKV challenge. The Matrix-M adjuvant elicited the highest magnitudes of anti-CHIKV IgG titers, and as in a recent preclinical study with an influenza virus antigen, formulation with Matrix-M induced a balanced IgG1/IgG2c ratio (52).…”
Section: Discussionmentioning
confidence: 99%
“…179). Strain 181/25 is attenuated but immunogenic in both mice and NHPs (138,179,180), and vaccination with 181/25 protects NHPs against CHIKV challenge (179). Strain 181/25 showed no adverse effects in a phase I clinical trial (181), and although it was highly immunogenic in phase II clinical trials, approximately 8% of subjects developed mild, transient arthralgia (182).…”
Section: Prospective Chikv Treatments and Vaccinesmentioning
confidence: 99%
“…Assays to assess the effect of heparin on virus infection were performed as previously described (39). Virus was diluted to an MOI of 2.5 in Opti-MEM (Invitrogen) and then mixed with either heparin or bovine serum albumin (BSA; final concentration, 200 g/ml).…”
Section: Methodsmentioning
confidence: 99%